The influence of playing training methods on shooting ability - Arifan, Ikhwanul; Soniawan, Vega; Qadafi, Muhammad; Okilanda, Ardo; Fernandes, Oca; Tofikin, Tofikin (Jurnal Patriot, 2024)
Problems: the weak shooting ability of SSB Putra Wijaya West Sumatra players, it can be seen that when athletes shoot, there are still many players who often lose the moment when taking a kick, so that the kick is not optimal. The variables of this research are Playing Training Method as the independent variable (X) and Shooting Ability as the dependent variable (Y). Purpose: The purpose of this research is to determine the effect of playing training methods on the shooting ability of SSB Putra Wijaya West Sumatra players. Method: This type of research is a quasi-experiment with a One group Pre-test-Post-test design. The population in this study were all SSB football players numbering 49 people. The sampling technique used purposive sampling technique, so the number of samples in this study was 17 players. The instrument in this research was to use a test of kicking a ball at a target (Shooting Target). The data analysis technique used in this research is the t-test with a significance level of α=0.05. Results: Based on data analysis in this study using the t-test, the playing training method had a significant influence on improving the shooting ability of SSB Putra Wijaya West Sumatra players, and this was proven by obtaining tcount= 6.001 while ttabe= 1.746. In practice there was an increase from the pretest average of 4.76 to 9.88 in the posttest. Then tcount > ttable (6,001>1,746). Conclusion: the ability to shoot is greatly influenced by the training program provided, one of which is using the playing method, so that in order to improve shooting skills, it is best to provide a training method that leads to the game of football itself, namely by providing training using the playing method, so that in its implementation, the shooting skills carried out will be improved properly